Discriminating Bacterial and Viral Infection Using a Rapid Host Gene Expression Test*. Issue 10 (29th April 2021) - Tsalik, Ephraim L.; Henao, Ricardo; Montgomery, Jesse L.; Nawrocki, Jeff W.; Aydin, Mert; Lydon, Emily C.; Ko, Emily R.; Petzold, Elizabeth; Nicholson, Bradly P.; Cairns, Charles B.; Glickman, Seth W.; Quackenbush, Eugenia; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Host gene expression signatures discriminate bacterial and viral infection but have not been translated to a clinical test platform. This study enrolled an independent cohort of patients to describe and validate a first-in-class host response bacterial/viral test. DESIGN: Subjects were recruited from 2006 to 2016. Enrollment blood samples were collected in an RNA preservative and banked for later testing. The reference standard was an expert panel clinical adjudication, which was blinded to gene expression and procalcitonin results. SETTING: Four U.S. emergency departments. PATIENTS: Six-hundred twenty-three subjects with acute respiratory illness or suspected sepsis. INTERVENTIONS: Forty-five–transcript signature measured on the BioFire FilmArray System (BioFire Diagnostics, Salt Lake City, UT) in 45 minutes. MEASUREMENTS AND MAIN RESULTS: Host response bacterial/viral test performance characteristics were evaluated in 623 participants (mean age 46 yr; 45% male) with bacterial infection, viral infection, coinfection, or noninfectious illness. Performance of the host response bacterial/viral test was compared with procalcitonin. The test provided independent probabilities of bacterial and viral infection in 45 minutes. In the 213-subject training cohort, the host response bacterial/viral test had an area under the curve for bacterial infection of 0.90 (95% CI, 0.84–0.94) and 0.92 (95% CI, 0.87–0.95) for viral infection. Independent validation in 209 subjects revealed similar performance with an area under the curve of 0.85 (95% CI, 0.78–0.90) for bacterial infection and 0.91 (95% CI, 0.85–0.94) for viral infection. The test had 80.1% (95% CI, 73.7–85.4%) average weighted accuracy for bacterial infection and 86.8% (95% CI, 81.8–90.8%) for viral infection in this validation cohort. This was significantly better than 68.7% (95% CI, 62.4–75.4%) observed for procalcitonin ( p < 0.001). An additional cohort of 201 subjects with indeterminate phenotypes (coinfection or microbiology-negative infections) revealed similar performance. CONCLUSIONS: The host response bacterial/viral measured using the BioFire System rapidly and accurately discriminated bacterial and viral infection better than procalcitonin, which can help support more appropriate antibiotic use.